Radiation exposure to the surgeon during axillary sentinel lymph node biopsy - Harran, Nadine (My University, 2014)
Introduction To measure the radiation exposure to the surgeon during axillary sentinel lymph node biopsy using the radioactive isotope technetium-99m. Method A prospective analysis of 36 patients undergoing axillary sentinel lymph node biopsy using technetium-99m, between 15th January 2013 to the 20th February 2013.. Results The exposure to the surgeon during axillary sentinel lymph node dissection was measured in 36 patients by placing a thermoluminescent dosimeter (TLD) on the surgeon’s finger. The TLDs recorded the total radiation exposure to the surgeon. The recommended occupational dose limit for non radiation workers extremity exposure is less than 500 μSv. The analysed and extrapolated data showed an average exposure dose to the surgeon per patient of 2.7 μSv. Conclusion One surgeon would need to perform more than 85 such procedures per year in order to exceed the advised annual extremity dose limit. The data also suggests that regular measurements of radiation exposure and radiation protective measures need not be undertaken in theatres where surgeons are working with radioactive isotope for axillary sentinel lymph node biopsies.
Keywords: Radiation Effects; Lymph Nodes--radiography